2021
DOI: 10.3389/fped.2021.626165
|View full text |Cite
|
Sign up to set email alerts
|

Performance of PRISM III, PELOD-2, and P-MODS Scores in Two Pediatric Intensive Care Units in China

Abstract: Objective: The performances of the pediatric risk of mortality score III (PRISM III), pediatric logistic organ dysfunction score-2 (PELOD-2), and pediatric multiple organ dysfunction score (P-MODS) in Chinese patients are unclear. This study aimed to assess the performances of these scores in predicting mortality in critically ill pediatric patients.Methods: This retrospective observational study was conducted at two tertiary-care PICUs of teaching hospitals in China. A total of 1,253 critically ill pediatric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…However, we were not able to confirm the association between albumin and mortality. Several studies and meta-analyses ( 32 34 ) showed PRISM-III had good performance for mortality prediction in PICU. In our study, we confirmed that PRISM-III can be served as the indicator to an independently predictor of mortality.…”
Section: Discussionmentioning
confidence: 99%
“…However, we were not able to confirm the association between albumin and mortality. Several studies and meta-analyses ( 32 34 ) showed PRISM-III had good performance for mortality prediction in PICU. In our study, we confirmed that PRISM-III can be served as the indicator to an independently predictor of mortality.…”
Section: Discussionmentioning
confidence: 99%
“…This was confirmed through the Hosmer-Lemeshow goodness-of-fit test (PRISM III: χ2 = 5.667, p = 0.368; PELOD-2: χ2 = 9.582, p = 0.276). 24 In this study, the free hormone variable (FT3) investigation was deemed more effective in assessing thyroid hormone function. This is because free hormones can penetrate cells and carry out their biological functions.…”
Section: Resultsmentioning
confidence: 99%
“…The study flow diagram is shown in Figure 1 . A total of 29 studies were included for quantitative synthesis, among them, 18 studies that reported on the scoring systems PRISM-III/IV, ( 3 , 4 , 11 , 14 – 21 , 23 27 , 37 ), 11 studies that reported data on PIM-3 ( 3 , 4 , 7 , 14 , 16 , 18 , 20 , 28 – 31 ), and nine studies that reported data on PELOD-2 ( 5 , 14 , 16 , 28 , 32 36 ). Four studies were reported from India ( 4 , 7 , 17 , 34 ), two from Australia ( 20 , 32 ), two from China ( 20 , 32 ), two from Egypt ( 15 , 18 ), one from Pakistan ( 19 , 26 ), two from Korea ( 14 , 36 ), one from Mexico ( 21 ), one from Singapore ( 28 ), one from UAE ( 29 ), one from Indonesia ( 30 ), one from Africa ( 33 ), one from Saudi Arabia ( 11 ), two from Turkey ( 22 , 24 ), one from Sweden ( 23 ), one from Brazil ( 37 ), one from Switzerland ( 5 ), one from Thailand ( 27 ), one from Italy ( 31 ), and one multi-centric ( 25 ).…”
Section: Resultsmentioning
confidence: 99%